Solve by factorization 6x^{2}+x-2=0

Katherine Walls 2021-12-16 Answered
Solve by factorization
6x2+x2=0
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

John Koga
Answered 2021-12-17 Author has 33 answers
Step 1
factor the following 6x2+x2=0
Step 2
Factor the quadratic 6x2+x2
The coefficient of x2 is 6 and the constant term is -2.
The product of 6 and -2 is -12. The factors of -12 which sum to 1 are -3 and 4.
So 6x2+x2=6x2+4x3x2=2(2x1)+3x(2x1):
2(2x-1)+3x(2x-1):
Factor 2x-1 from 2(2x-1)+3x(2x-1)=(2x-1)(3x+2);
=(2x-1)(3x+2)
Now set (2x-1)(3x+2)=0
(2x-1)=0 and (3x+2)=0
x=12 and x=23

We have step-by-step solutions for your answer!

Samantha Brown
Answered 2021-12-18 Author has 35 answers
Step 1
The given equation is
6x2+x2=0
Step 2
6x2+(43)x2=0
6x2+4x3x2=0
2x(3x+2)1(3x+2)=0
(3x+2)(2x1)=0
So
(3x+2)=0. Or (2x-1)=0
x=-2/3, 1/2

We have step-by-step solutions for your answer!

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

New questions